A remarkable new species of Chalcosyrphus Curran from the Oriental Region (Diptera: Syrphidae) - Hauser, Martin; Hippa, Heikki (Zootaxa, 2015)
Chalcosyrphus blanki sp. nov. is described from material collected in China, Thailand and Burma. The new species is outstanding because of its size and metallic blue coloration. It is remarkable that only a few specimens have been found so far, all from different countries and only with Malaise traps. The species was only collected at altitudes above 2500 m. It fits very well in the genus Chalcosyrphus, but cannot be placed in any existing subgenus.